The content of arbutin in the leaves of a bearberry Arctostaphylos Uva-ursi with different regions of Ukraine - Колесник, Ю. А. (Problems of Environmental Biotechnology, 2014)
The content of arbutin in bearberry leaves that grew in different regions of Ukraine: Lviv region, Korostishev city; Khmelnytskyi region, the town of Slavuta and Cherkasy region, Zvenigorod district, the village of Tarasovka, was investigated.